2020
DOI: 10.3390/en13030685
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Statistic Based Risk Assessment Approach to Prioritize the Pipeline Inspection of the Pipeline Network

Abstract: The identification of high risk regions is an important aim of risk-based inspections (RBIs) in pipeline networks. As the most vital part of risk-based inspections, risk assessment makes a significant contribution to achieving this aim. Accurate assessment can target high risk inspected regions so that limited resources can mitigate considerable risks in the face of increased spatial distribution of a pipeline network. However, the existing approaches for risk assessment face grave challenges due to a lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, difficulty arises when selecting proper tools to measure the risk and the actual method to capture the risk level of inspected pipelines. An option to overcome the relevant difficulties can be developing a Risk-based inspection using a risk matrix and generating data through inline Inspection as reported by [20]. The study [21] shows that the RBI is essential to replace the existing time-based Inspection.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…However, difficulty arises when selecting proper tools to measure the risk and the actual method to capture the risk level of inspected pipelines. An option to overcome the relevant difficulties can be developing a Risk-based inspection using a risk matrix and generating data through inline Inspection as reported by [20]. The study [21] shows that the RBI is essential to replace the existing time-based Inspection.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…[14] established that the pipe age influenced sewer pipe condition and found that poor pipe sewer condition is higher for pipes more than 50 years. "Most of the condition prediction models developed in previous studies show that pipe age has a significant relationship with deterioration of sewer pipes" [15].…”
Section: Physical Factorsmentioning
confidence: 99%
“…Pipelines have become the main way of liquid transportation because of their advantages in economy and transportation capacity [1]. However, during the long-term operation of pipelines, they inevitably leak due to corrosion, third-party destruction and natural disasters, causing environmental contamination, fires or explosions if measures are not taken in a timely way [2][3][4].…”
Section: Introductionmentioning
confidence: 99%